A rare case of alpha-thalassaemia intermedia in a Malay patient double heterozygous for α+ –thalassaemia and a mutation in α1 globin gene CD59 (GGC → GAC) - George, Elizabeth; Tan, Mary Anne Jin Ai; A. S., Nor Azian; Ahmad, Rahimah; Zakaria, Zubaidah (Malaysian Medical Association, 2009)
A rare case of thalassaemia-intermedia involving a non-deletion alpha thalassemia point mutation in the α1-globin gene CD59 (GGC → GAC) and a deletion α+ (-α3.7) thalassaemia in which use of high performance liquid chromatography (HPLC) C-gram Hb subtype profile and DNA molecular analysis helped establish the diagnosis.